2022
DOI: 10.3171/2021.10.focvid21196
|View full text |Cite
|
Sign up to set email alerts
|

5-ALA fluorescence in indeterminate grade gliomas

Abstract: 5-Aminolevulinic acid (5-ALA) is a useful and well-established adjunct for glioblastoma surgery. A growing body of evidence has revealed the potential utility of 5-ALA in grade II and grade III glioma patients as well. However, reliable means of identifying in whom fluorescence will occur have not been established. The authors report the case of such an indeterminate-grade glioma highlighting two pearls of 5-ALA fluorescence in this subgroup of patients. Firstly, 5-ALA–guided tissue sampling helps to ensure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…To prevent the underestimation of focal enhancing tumors, using 5-aminolevulinic acid (5-ALA) guided tissue sampling can be advantageous. This technique enhances the precision of biopsy sampling by making tumor cell visibility under uorescence, thereby improving diagnostic accuracy [30].…”
Section: Discussionmentioning
confidence: 99%
“…To prevent the underestimation of focal enhancing tumors, using 5-aminolevulinic acid (5-ALA) guided tissue sampling can be advantageous. This technique enhances the precision of biopsy sampling by making tumor cell visibility under uorescence, thereby improving diagnostic accuracy [30].…”
Section: Discussionmentioning
confidence: 99%
“…To prevent the underestimation of focal enhancing tumors, using 5-aminolevulinic acid (5-ALA) guided tissue sampling can be advantageous. This technique enhances the precision of biopsy sampling by making tumor cell visibility under fluorescence, thereby improving diagnostic accuracy [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, PDT-mediated injury of vessels is not specific and based on destructive effects of singlet oxygen and reactive oxygen species produced by photosensitizes after their photoexcitation [ 57 ]. Therefore, in this work, we used PDT with 5-ALA because this photosensitizer is used in clinical practice for PDT of glioblastoma [ 58 , 59 ]. Recently, we reported that PDT with 5-ALA causes dose- and age-related injuries of cerebral blood vessels leading to an increase in the permeability of blood–brain barrier [ 52 , 60 62 ].…”
Section: Discussionmentioning
confidence: 99%